2018
DOI: 10.1002/stem.2780
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of TAP1 in Aldefluor+ Breast Cancer Stem Cells Contributes to Their Enhanced Immune Evasion

Abstract: Avoiding detection and destruction by immune cells is key for tumor initiation and progression. The important role of cancer stem cells (CSCs) in tumor initiation has been well established, yet their ability to evade immune detection and targeting is only partly understood. To investigate the ability of breast CSCs to evade immune detection, we identified a highly tumorigenic population in a spontaneous murine mammary tumor based on increased aldehyde dehydrogenase activity. We performed tumor growth studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…BCSCs are resistant to chemotherapy and radiation [2,6,41,43] and recent studies demonstrated that BCSCs escape from innate and adaptive immune responses, which suggests that BCSCs are resistant to immunotherapy as well [44][45][46][47][48]. These findings underscore the importance of developing novel approaches that make BCSCs as sensitive as non-BCSCs to conventional therapies and immunotherapy in order to develop successful and curative treatments for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…BCSCs are resistant to chemotherapy and radiation [2,6,41,43] and recent studies demonstrated that BCSCs escape from innate and adaptive immune responses, which suggests that BCSCs are resistant to immunotherapy as well [44][45][46][47][48]. These findings underscore the importance of developing novel approaches that make BCSCs as sensitive as non-BCSCs to conventional therapies and immunotherapy in order to develop successful and curative treatments for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cell analysis and isolation of distinct cell populations using a FACSAria (BD Pharmingen) based on Aldefluor activity (Aldefluor assay kit, StemCell Technologies) was performed as per the manufacturer's instructions and as previously described [36,37]. To remove dead cells from the sorted populations, the cells were stained with 7-AAD.…”
Section: Aldefluor Sortingmentioning
confidence: 99%
“…Of the breast cancer subtypes, TNBC/basal-like breast cancers have higher percentages of CSCs, which may contribute to their aggressiveness and the worse patient outcomes associated with these breast cancers (17)(18)(19)(20)(21)(22)(23). In terms of mitigating the risk of recurrence, the resistance of CSCs to chemotherapies, radiotherapy, and possibly immunotherapies is an increasing concern (24)(25)(26)(27)(28)(29). Therapies that target CSCs may reduce the risk of relapse.…”
Section: Breast Cancer Stem Cells: Inherent Metabolic Plasticitymentioning
confidence: 99%